2D Metal Chalcogenides Incorporated into Carbon and their Assembly for Energy Storage Applications. Issue 22 (30th April 2018) - Deng, Zongnan; Jiang, Hao; Li, Chunzhong
Abstract: 2D metal chalcogenides have become a popular focus in the energy storage field because of their unique properties caused by their single‐atom thicknesses. However, their high surface energy and van der Waals attraction easily cause serious stacking and restacking, leading to the generation of more inaccessible active sites with rapid capacity fading. The hybridization of 2D metal chalcogenides with highly conductive materials, particularly, incorporating ultrasmall and few‐layered metal chalcogenides into carbon frameworks, can not only maximize the exposure of active sites but also effectively avoid their stacking and aggregation during the electrochemical reaction process. Therefore, a satisfactory specific capacity will be achieved with a long cycle life. In this Concept, the representative progress on such intriguing nanohybrids and their applications in energy storage devices are mainly summarized. Finally, an outlook of the future development and challenges of such nanohybrids for achieving an excellent energy storage capability is also provided. Abstract : A representative progress of 2D metal chalcogenides incorporated in carbon and their assembly is summarized. These hybrids are very promising for traditional and flexible energy storage devices. The existing challenges, improvement suggestions, and future perspectives are also provided.